Efeito da concentração de ácido fluorídrico e do tempo de condicionamento na adesão e no comportamento mecânico de cerâmicas vítreas: revisão sistemática e meta-análise - Riesgo, Bibiana Vogel Peres (2021)
The aim of this study was to compare the effects of different concentrations and etching times with hydrofluoric acid on the bond strength to resin cements and on the mechanical behavior of feldspathic, leucite-reinforced glass-ceramic, lithium disilicate and lithium silicate-based glass-ceramics through a systematic review of the literature. The search was performed in LILACS, PubMed/Medline, Scopus and Web of Science databases. The search strategy was carried out in two stages (title and abstract reading, and complete reading), which were conducted by two reviewers independently. In vitro studies that evaluated the effect of etching times or hydrofluoric acid concentrations on the adhesive or mechanical behavior of glass ceramics were included. Studies should present at least one protocol recommended by the manufacturers or frequently found in the literature (control) and an alternative protocol (intervention). From 3375 potentially selected studies, 86 were selected for full-text analysis, 28 were included for qualitative synthesis, from which 21 were used in the meta-analysis. Five studies that evaluated mechanical behavior through flexural fatigue strength and fatigue failure load tests were included in the qualitative analysis. Ten meta-analyses were carried out, from which eight involved comparisons of adhesive strength and the data were grouped according to the type of ceramic, to the factor under analysis (HF concentration and conditioning time) and to the aging conditions of the specimens. Heterogeneities ranged from high to low. In general, no statistical difference was observed in bond strength between the alternative application protocols of hydrofluoric acid and the control group, indicated by the manufacturer 5% for a time of 60 seconds in feldspathic and leucite-reinforced glassceramic. The meta-analysis performed for lithium disilicate-based ceramic showed, in the global analysis, a favoring of the time recommended by the manufacturer, 5% HF protocol for 20 seconds (p=0.005), compared to the times of 40 and 60 seconds. For the 10% concentration in the etching of lithium disilicate-based and lithium silicate-based ceramics, the global analysis showed favoring the 20- second comparison group, however the subgroup analyzes did not show any statistical difference in the bond strength. For the same ceramic, decreasing flexural strength was observed when the specimens were conditioned to times longer than that recommended by the manufacturers. In addition, there was a significant favoring for the HF concentration recommended by the manufacturer when compared to higher concentrations. The concentration and application time of hydrofluoric acid on lithium disilicate and lithium silicate ceramics recommended by the manufacturers appear to be effective in providing bond strength and mechanical strength values similar to or greater than alternative protocols. The effects of the etching protocols were no different regarding bond strength of feldspathic and leucite-reinforced glass-ceramics. In addition, it was not possible quantitatively evaluating the variable effects on the mechanical behavior of these ceramics.